PENGEMBANGAN MEDIA VIDEO ANIMASI PADA PEMBELAJARAN TEMATIK BERBASIS PENDEKATAN SAINTIFIK DI KELAS IV SDN 35 AMBACANG KAMBA - Puspita, Vivi; Yuni, Rahma (LP2M Universitas Adzkia, 2024)
This study was motivated by the importance of instructional media used by teachers in the learning process. The main objective is to develop an animated video-based thematic learning media for fourth-grade elementary students. This research is a type of Research and Development (R&D) using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The trial was conducted on nine fourth-grade students. Instruments used include validation sheets, practicality questionnaires for teachers and students, and effectiveness tests using daily assessment items. Validation results showed the animated video media was highly valid, with scores of 91% from the design expert, 100% from the content expert, and 97% from the language expert, with an overall average of 96%. The practicality score was 94% from teachers and 89% from students, both categorized as very practical. The effectiveness score was 89%, indicating high effectiveness. Therefore, the developed animated video media is highly valid, practical, and effective.